Beyond information: Disclosure, distracted attention, and investor behavior / Adrian Hillenbrand - Adrian Hillenbrand; André Schmelzer (Max Planck Institute for Research on Collective Goods, 2015)
Financial disclosure documents provide investors with product details to facilitate informed investment decisions. We investigate whether the appearance - the visual frame - of disclosure documents impacts risk and return expectations and investment behavior. In our experiment, subjects decide about investments into real-life mutual funds. We find that subjects expect a smaller return variance, invest more and gather less correct information if visual distractors are present in the visual frame. Results are in line with the distracted attention mechanism and suggest that disclosure policies should take the visual frame into account.
Keywords: C91; D03; D14; D18; D84; 330; portfolio choice; experiment; disclosure; mean-variance theory; attention